Revitalisasi Seni Budaya Wayang melalui Tayangan Televisi - Agus Maladi Irianto (Nusa: Jurnal Ilmu Bahasa dan Sastra, 2018)
AbstractThe development of traditional art is the development of artistic values and art appreciation in order to increase the artist and community's friendship. Ideally the arts as part of the national culture derive its meaning in terms of understanding and appreciation of cultural values. Therefore, to improve the resilience of the nation's culture, then the national development needs to be dotted from the efforts of art development that can give birth to "cultural value-added". Artistic gifts (local and national) are essentially necessary, because they are rooted in the culture of society. However, it is possible for decomposition, reconstruction, recoreography, renovation, revitalization, refunctionalization, along with improvisations with various ornaments. This is where local art becomes cultural property and socio-cultural "capital" of society. For this reason, a strategy is needed so that regional art can be placed as a means of creating a nation's cultural resilience. One of them is to revitalize the art of wayang culture through television shows. IntisariPengembangan kesenian tradisonal adalah pembangunan nilai-nilai seni dan apresiasi seni demi meningkatkan kemartabatan seniman dan masyarakat. Idealnya kesenian sebagai bagian dari kebudayaan nasional memperoleh maknanya dalam kaitan dengan pemahaman dan apresiasi nilai-nilai kultural. Oleh karena itu, untuk  meningkatkan ketahanan budaya bangsa, maka pembangunan nasional perlu bertitik-tolak dari upaya-upaya pengembangan kesenian yang mampu melahirkan “nilai-tambah kultural”. Pakem-pakem kesenian (lokal dan nasional) pada dasarnya tetap diperlukan, karena ia berakar dalam budaya masyarakat. Akan tetapi, ia dimungkinkan untuk dekomposisi, rekonstruksi, rekoreografi, renovasi, revitalisasi, refungsionalisasi, disertai improvisasi dengan aneka hiasan. Di sinilah kesenian daerah menjadi kekayaan budaya dan “modal sosial-kultural” masyarakat. Untuk itulah,diperlukan sebuah strategi agar kesenian daerah dapat ditempatkan sebagai sarana menciptakan ketahanan budaya suatu bangsa. Salah satu di antaranya adalah dengan melakukan revitalitasi seni budaya wayang  melalui tayangan televisi